2010
DOI: 10.1111/j.1778-428x.2010.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anemia in elective cardiac surgery: prevalence, risk factors, and influence on postoperative outcome

Abstract: Keywords• allogeneic blood transfusion • cardiac surgery • postoperative outcome • preoperative anemia S U M M A R YPreoperative anemia in patients undergoing cardiac surgery is associated with a higher transfusion risk and poorer outcomes. This retrospective study was undertaken to assess the prevalence of preoperative anemia and its associated risk factors, as well as its influence on postoperative outcomes, in 576 patients undergoing elective cardiac surgery (52.3% with cardiopulmonary bypass) for myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Characteristics of the included studies are summarized in Table . A total of 949 445 patients were included, and all 24 studies reported the primary outcome of 30‐day or in‐hospital mortality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Characteristics of the included studies are summarized in Table . A total of 949 445 patients were included, and all 24 studies reported the primary outcome of 30‐day or in‐hospital mortality.…”
Section: Resultsmentioning
confidence: 99%
“…However, stroke and myocardial infarction were reported as an outcome only in studies of patients undergoing cardiac surgery ( Table ). A haemoglobin definition was used in 17 studies, a haematocrit definition in six studies, and both definitions were used in one study. Definitions of anaemia ranged from a haemoglobin concentration of 11 to 12 g/dl or a haematocrit of 30–39 per cent for female patients, and from 11 to 14 g/dl or 30–39 per cent respectively for male patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anemia is a recognized risk factor for operative mortality; additionally serious and invalidating postoperative morbidity like stroke, myocardial infarction, and renal failure have been described. [1][2][3][4] Transfusions with red blood cells (RBCs) serve to prevent the occurrence of anemia-related complications, but have also been associated with severe side effects. 5,6 Therefore, it is sometimes unclear whether an anemic patient will benefit from a RBC transfusion or not.…”
mentioning
confidence: 99%